Effects of preparation method on the microstructure and photocatalytic performance of ZnSn(OH)6 - Fu, Xianliang; Huang, Danwei; Qin, Yong; Li, Longfeng; Jiang, Xiaoliang; Chen, Shifu (Applied catalysis. B, Environmental, 2014)
The surface microstructure and the photocatalytic performance of ZHS are sensitive to the preparation methods. •ZHS surface microstructure and photocatalytic performance are sensitive to preparation method.•A harsh preparation condition leads to OH-unsaturated Zn and Sn atoms.•ZHS prepared by PVP-assisted hydrothermal method exhibits the highest activity. It is indispensable to find a suitable preparation method to optimize the photocatalyst performance. Different ZnSn(OH)6 (ZHS) were prepared by four methods in this report, including grinding, co-precipitation, self-templating, and hydrothermal processes. The crystal structures, optical properties, thermal stabilities, and morphologies of the ZHS samples were investigated systematically. Photocatalytic degradation of methyl orange (MO) and gaseous benzene (C6H6) over the samples were assessed and compared. The relationship between the microstructure and the photocatalytic performance of ZHS was analyzed. The results reveal the surface microstructure and the photocatalytic performance of ZHS are more sensitive to the preparation methods than the crystal structure and the morphology. A harsh preparation condition leads to the formation of some OH-unsaturated Zn and Sn atoms due to the susceptible of OH groups, which result in a tail light absorption of ZHS and are assumed as the photoactive center. ZHS prepared by the PVP-assisted hydrothermal method exhibits the highest thermal stability, optical absorption, BET surface area and ability for O2 activation, and consequently shows the highest photocatalytic activity and stability for the degradation of MO and gaseous C6H6.